Measuring brand image using a cognitive approach: Representing brands as a network in the Turkish airline industry - DİRSEHAN, TAŞKIN (ELSEVIER SCI LTD, 2018)
This study extends the previous brand image measurement processes by using a mixed (qualitative and quantitative) methodology, drawing upon a cognitive approach to represent consumers' minds as a network. Therefore, three consecutive studies have been designed from a sample of 1000 passengers to construct four distinct concept maps and a common one pertaining to four Turkish airline companies. The results show the importance of increasing flight comfort, training cabin crew, providing free appetizers, improving service quality, and ensuring timely departures in creating and sustaining a positive brand image. Academicians could use this methodology as an alternative technique to the traditional ones and practitioners could use it to evaluate brands' competitive advantages to create powerful brand images in consumers' minds.
Keywords: Brand association; Brand image; Cognitive learning; Concept map; Turkish airline industry; CUSTOMER LOYALTY; DOMINANT LOGIC; CONCEPT MAPS; EQUITY; PERCEPTIONS; IMPACT